Using gnotobiotic mice to decipher effects of gut microbiome repair in undernourished children on tuft and goblet cell function - Yi Wang; Hao-Wei Chang; Jiye Cheng; Daniel M. Webber; Hannah M. Lynn; Matthew C. Hibberd; Clara Kao; Ishita Mostafa; Tahmeed Ahmed; Michael J. Barratt; Jeffrey I. Gordon (Proceedings of the National Academy of Sciences, 2025)
Studies have implicated perturbations in the postnatal development of the gut microbiome as a contributing factor to childhood undernutrition. Compared to a standard ready-to-use supplementary food, a microbiome-directed complementary food (MDCF-2) designed to repair these perturbations produced superior improvements in ponderal and linear growth in clinical trials of Bangladeshi children with moderate acute malnutrition. Here, “reverse translation” experiments are performed where intact fecal microbiomes collected from trial participants before and at the end of treatment are introduced into female gnotobiotic mice just after delivery of their pups. Pups received diets designed to resemble those consumed by children in the trials to recreate “unrepaired” and “repaired” gut ecosystems. Analyses of the abundances of bacterial strains (metagenome-assembled genomes), their expressed genes, and metabolic products, combined with assessments of ponderal growth and intestinal epithelial lineage transcriptomes (single-nucleus RNA-Seq with follow-up immunocytochemistry) disclosed effects of MDCF-2 associated microbiome repair that cannot be determined, in part because “no treatment” control arms cannot be ethically incorporated into these trials. Specifically, microbiome repair in these mice produced significant increases in ponderal growth, changes in microbial gene expression consistent with a less virulent gut ecosystem and alterations in expression of i) components of cell junctions in the enterocytic and goblet cell lineages, ii) pathways for synthesis and secretion of eicosanoid immune effectors in chemosensory tuft cells, and iii) goblet cell pathways involved in glycosylation and secretion of mucin. Experiments of the type described can help formulate and test hypotheses about how microbiome repair affects host biology.